Shlomo Aronson, The Politics and Strategy of Nuclear Weapons in the Middle East: Opacity, Theory and Reality, 1960-1991, New York: State University of New York Press, 1992, 398 s., 21.95. - van Dassen, Lars (Politica, 1994)
-